BADAN PENYELENGGARA JAMINAN PRODUK HALAL DALAM MENSOSIALSIASIKAN URGENSI HALAL BAGI PELAKU USAHA MIKRO KECIL DAN MENENGAH - Hardiansyah, Tubagus Rizki; Yazid, Muhammad; Sikumbang, Thamrin (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
The heterogeneity of society in their social activities does not always have a positive impact on the Muslim community in Binjai City, because heterogeneous associations can cause some Muslims to lose awareness in consuming products that are not labeled halal. So in a situation like this, it is important for the Halal Assurance Organizing Agency to Socialize the urgency of halal products for the community about the importance of consuming halal products, increase awareness, empower consumers, collaborate with the Binjai City government and related institutions, and strengthen the certification and monitoring system. This study aims to determine the efforts of the Halal Assurance Organizing Agency of Binjai City in Socializing the urgency of halal products. This study uses a qualitative descriptive approach with a phenomenological research type. Primary data in this study is information and phenomena obtained directly, while secondary data in this study includes documents and relevant literature. Data collection in this study uses semi-structured interviews and non-participant observation. The data validity checking technique in this study uses triangulation techniques. The results of this study indicate that the Halal Assurance Agency of Binjai City has made comprehensive communication efforts in socializing the Muslim community about the urgency of consuming halal products. The efforts of the Ministry of Religion include counseling, halal certification, social media campaigns, cooperation with industry and trade, supervision, law enforcement, and collectivity through communication in social groups.